DETERMINAN KEMISKINAN DI KABUPATEN SANGGAU - B2051131003, SIKAI (Jurnal Ekonomi Daerah (JEDA), 2016)
This Thesis  entitle "The Determinants of  Poverty in Sanggau Regency" This is a study that aimed to examine the causal factors of poverty in Sanggau regency. Data sourced from The data base of the Target Families Social Direct Protection Prorgam (PPLS) in year 2008, 2011 and 2012, that taken from 15 districts. The analysis used is multiple regression with dependent varibabel are  level of health, education and GRDP (Gros Regional Domestic Product). The results of  partial analysis (test) shows that there is positive effect but not significant from the health level, and there was a negative effect and significant impact on the level of education, and there was a positive and significant effect of GRDP on poverty in Sanggau Regency. The results of simultaneously (together) test  (Ftest) thatall of  three variables showed a significant effect. The relationship of all the variables indicated by the coefficient of determination adjR2 as 0.178. That is the effect of them three variables (health, education and GRDP) against poverty was 17.80%, while the rest (82.20%) are influenced by other factors. Keywords : Poor Family, GRDP, literacy rate, life expectancy